Eosinophil-mediated signalling attenuates inflammatory responses in experimental colitis. Issue 8 (10th September 2014) - Masterson, Joanne C; McNamee, Eóin N; Fillon, Sophie A; Hosford, Lindsay; Harris, Rachel; Fernando, Shahan D; Jedlicka, Paul; Iwamoto, Ryo; Jacobsen, Elizabeth; Protheroe, Cheryl; Eltzschig, Holger K; Colgan, Sean P; et al.
Abstract : Objective: Eosinophils reside in the colonic mucosa and increase significantly during disease. Although a number of studies have suggested that eosinophils contribute to the pathogenesis of GI inflammation, the expanding scope of eosinophil-mediated activities indicate that they also regulate local immune responses and modulate tissue inflammation. We sought to define the impact of eosinophils that respond to acute phases of colitis in mice. Design: Acute colitis was induced in mice by administration of dextran sulfate sodium, 2, 4, 6-trinitrobenzenesulfonic acid or oxazolone to C57BL/6J (control) or eosinophil deficient ( PHIL ) mice. Eosinophils were also depleted from mice using antibodies against interleukin (IL)-5 or by grafting bone marrow from PHIL mice into control mice. Colon tissues were collected and analysed by immunohistochemistry, flow cytometry and reverse transcription PCR; lipids were analysed by mass spectroscopy. Results: Eosinophil-deficient mice developed significantly more severe colitis, and their colon tissues contained a greater number of neutrophils, than controls. This compensatory increase in neutrophils was accompanied by increased levels of the chemokines CXCL1 and CXCL2, which attract neutrophils. Lipidomic analyses of colonic tissue from eosinophil-deficient mice identified a deficiency in the docosahexaenoic acid-derived anti-inflammatory mediator 10, 17- dihydroxydocosahexaenoic acid (diHDoHE), namely protectin D1 (PD1). Administration of an exogenous PD1-isomer (10S, 17S-DiHDoHE) reduced the severity of colitis in eosinophil-deficient mice. The PD1-isomer also attenuated neutrophil infiltration and reduced levels of tumour necrosis factor-α, IL-1β, IL-6 and inducible NO-synthase in colons of mice. Finally, in vitro assays identified a direct inhibitory effect of PD1-isomer on neutrophil transepithelial migration. Conclusions: Eosinophils exert a protective effect in acute mouse colitis, via production of anti-inflammatory lipid mediators.